Pulse Pressure Index as a Discriminator of Predicting the Cardiovascular Events in Hypertensive Patients Treated with Drugs Acting on Angiotensinogen-Angiotensin Pathway - Marwan S. Al-Nime; Ismail I. Hussein; Yagub S. Saleh (Al-Anbar Medical Journal)
Background: Pulse pressure index as a function of pulse pressure divided by systolic blood pressure served is a useful predictor of cardiovascular events. Objectives: Our aim was to assess the pulse pressure index as a discriminating variable of predicting cardiovascular events in untreated or hypertensive patients and treated with one member of angiotensin converting enzyme inhibitors or angiotensin receptor blockers by using the scores of Framingham study. Materials and methods: This observational cross-sectional study, including 140 patients who grouped into; Group I (n = 30): untreated hypertensive patients; Group II (n = 60): patients treated with angiotensin receptor blockers; and Group III (n = 50): patients treated with angiotensin converting enzyme inhibitors. Anthropometric measurements, lipid profile, and blood pressure were determined. The probability of ten-year of cardiovascular events was calculated according to the Framingham study scores using The University of Edinburgh Cardiovascular Risk Calculator (http://cvrisk.mvm.ed.ac.uk/calculator/calc.asp).  Results: There is a non-significant difference between Groups and within Groups of age, smoking habit, and the values of the cardio metabolic risk factors. Pulse pressure index as an independent risk factor found to be a significant discriminator of 10-year prediction of cardiovascular events by using the receiving operating characteristic curves. Conclusion: The pulse pressure index is a useful discriminator of predicting cardiovascular events, and it will improve the Framingham prediction risk among hypertensive patients.